Identification of Anti-Mycobacterium and Anti-Legionella Compounds With Potential Distinctive Structural Scaffolds From an HD-PBL Using Phenotypic Screens in Amoebae Host Models - Hanna, Nabil; Kicka, Sébastien; Chiriano, Gianpaolo; Harrison, Christopher; Sakouhi, Hajer Ouertatani; Trofimov, Valentin; Kranjc, Agata; Nitschke, Jahn; Pagni, Marco; Cosson, Pierre; Hilbi, Hubert; Scapozza, Leonardo; et al. (Frontiers in Microbiology, 2020)
Tubercular Mycobacteria and Legionella pneumophila are the causative agents of potentially fatal respiratory diseases due to their intrinsic pathogenesis but also due to the emergence of antibiotic resistance that limits treatment options. The aim of our study was to explore the antimicrobial activity of a small ligand-based chemical library of 1,255 structurally diverse compounds. These compounds were screened in a combination of three assays, two monitoring the intracellular growth of the pathogenic bacteria, Mycobacterium marinum and L. pneumophila, and one assessing virulence of M. marinum. We set up these assays using two amoeba strains, the genetically tractable social amoeba Dictyostelium discoideum and the free-living amoeba Acanthamoeba castellanii. In summary, sixty-four (5.1%) compounds showed anti-infective/anti-virulence activity in at least one of the 3 assays. The intracellular assays hit rate varied between 1.7% (n=22) for M. marinum and 2.8% (n=35) for L pneumophila with 7 compounds in common for both pathogens. In parallel, 1.2 % (n= 15) of the tested compounds were able to restore D. discoideum growth in the presence of M. marinum spiked in a lawn of food bacteria. We also validated the generality of the hits identified in the A. castellanii-M. marinum anti-infective screen using the D. discoideum-M. marinum host-pathogen model. The characterization of anti-infective and antibacterial hits in the latter infection model revealed compounds able to reduce intracellular growth more than 50% at 30 M. Moreover, the chemical space and physico-chemical properties of the anti-M. marinum hits were compared to standard and candidate M. tuberculosis drugs using ChemGPS-NP. A principle component analysis identified separate clusters for anti-M. marinum and anti-L. pneumophila hits unveiling the potentially new physico-chemical properties of these hits compared to standard and candidate M. tuberculosis drugs. Our studies underscore the relevance of using a combination of low-cost and low-complexity assays with full 3R compliance in concert with a rationalized focused library of compounds to identify new chemical scaffolds and to dissect some of their properties prior to taking further steps towards compound development.